"After‐hours" staffing of trauma centres and outcomes among patients presenting with acute traumatic coagulopathy. Issue 10 (17th November 2014) - Mitra, Biswadev; Cameron, Peter A; Fitzgerald, Mark C B; Bernard, Stephen; Moloney, John; Varma, Dinesh; Tran, Huyen; Keogh, Martin
Abstract: Objective: To examine the effect of the "after‐hours" (18:00–07:00) model of trauma care on a high‐risk subgroup — patients presenting with acute traumatic coagulopathy (ATC). Design, participants and setting: Retrospective analysis of data from the Alfred Trauma Registry for patients with ATC presenting between 1 January 2006 and 31 December 2011. Main outcome measure: Mortality at hospital discharge, adjusted for potential confounders, describing the association between after‐hours presentation and mortality. Results: There were 398 patients with ATC identified during the study period, of whom 197 (49.5%) presented after hours. Mortality among patients presenting after hours was 43.1%, significantly higher than among those presenting in hours (33.1%; P = 0.04). Following adjustment for possible confounding variables of age, presenting Glasgow Coma Scale score, urgent surgery or angiography and initial base deficit, after‐hours presentation was significantly associated with higher mortality at hospital discharge (adjusted odds ratio, 1.77; 95% CI, 1.10–2.87). Conclusion: The after‐hours model of care was associated with worse outcomes among some of the most critically ill trauma patients. Standardising patient reception at major trauma centres to ensure a consistent level of care across all hours of the day may improve outcomes among patients who have had a severe injury.